Developing Risk Management Mechanism at Fat-and-Oil Industry Enterprises - Posokhov, Igor Mikhailovich; Zhadan, Yuliya; Korin, Myroslava; Obruch, Hanna (My University, 2019)
The aim of the article is consideration of questions associated with the risk management mechanism formation at the Ukrainian fat-and-oil industry enterprises, modern scientific publications on this topical subject and developing risk management mechanism for fat-and-oil industry enterprises in Ukraine. It has been determined the principles of risk management. It has been offered the risk management procedure at the level of the fat-and-oil industry enterprises, which includes the following stages: identification and evaluation of risks, development and analysis of risk management methods, choice of risk management methods, application of the selected methods, monitoring of the results and risk management system improvement. It has been developed the risk management mechanism of fat-and-oil industry enterprises, which allows to distinguish the main components of risk management and to increase their overall efficiency, as well as to facilitate understanding of the risk management mechanism essence and structure, which, in turn, reveals the direction for its improvement.
Keywords: risk; risk management; framework; fat-and-oil industry